Hemoglobin A1c and retinal arteriolar narrowing in children with type 1 diabetes: the diagnostics of early atherosclerosis risk in kids study. Issue 5 (20th May 2019) - Wurm, Michael; Kühnemund, Leonie; Maier, Lisa; Xia, Mi; Lichte, Kai; Hallermann, Kristiane; Krause, Alexandra; Krebs, Andreas; Hanssen, Henner; Deibert, Peter; Schwab, Karl Otfried
Abstract : Background/Objective: Microvascular alterations play a key role in the development of diabetes complications. Retinal vessel analysis is a unique method to examine microvascular changes in brain‐derived vessels. Methods: Sixty‐seven pediatric and adolescent type 1 diabetes patients and 58 healthy control persons (mean age 12.4 ± 2.9 years) underwent non‐mydriatic retinal photography of both eyes. Central retinal arteriolar and central retinal venular (CRVE) diameter equivalents as well as the arteriolar‐to‐venular ratio were calculated using a semiautomated software. All anthropometric and laboratory parameters were measured according to standardized procedures for children. Results: Retinal vessel diameter did not differ between type 1 diabetic children and healthy controls. However, there was an independent association of higher hemoglobin A1c (HbA1c) levels with arteriolar narrowing. Arteriolar narrowing of 5.4 μm was observed with each percent increase in HbA1c. Longer duration of diabetes was associated with wider retinal arterioles. CRVE was not associated with diabetes duration or HbA1c. Conclusions: Microvascular arteriolar alterations are already present in childhood and may indicate subclinical atherosclerosis and increased risk of diabetes complications later in life. Future research will have to investigate the potential use of retinal vessel diameters for treatment monitoring and guidance of therapy in children.